Longitudinal idiographic assessment of adolescent-dog relationships and adaptive coping for youth with social anxiety: The Teen & Dog Study protocol - Megan K. Mueller; Erin K. King; Linda Charmaraman; Jasmine Mote; Eric C. Anderson; Seana Dowling-Guyer; Nicole Mason; Jordanne J. N. Brown; Evan C. Mingo; Rachael A. Sabelli; Emily McCobb (PLoS ONE, 2025)
The Teen & Dog Study is a longitudinal research project aimed at understanding the impact of youth-dog relationships on youth coping with social anxiety. The study will follow 514 United States adolescents (ages 13–17) with high social anxiety who live with dogs and their families, collecting longitudinal assessments of their physiological, emotional, and social well-being. With a focus on identifying the mechanisms by which youth-dog interactions may support adaptive coping, the study has three primary aims: (1) assess how the youth-dog relationship contributes to coping with social anxiety over time, factoring in individual, family, and peer influences; (2) investigate family-level processes that enhance youth-dog relationships and identify barriers to optimization; and (3) examine how dog interactions influence adolescents’ physiological responses, particularly in relation to anxiety. The study integrates quantitative and qualitative data, including surveys, interviews, ecological momentary activity, and continuous physiological monitoring, to assess strategies for optimizing youth-dog interactions in the context of social anxiety. This paper outlines the study protocol and presents characteristics of the study sample at baseline. Ultimately, the Teen & Dog Study seeks to inform interventions that harness the benefits of youth-dog relationships to improve mental health outcomes.